1999
DOI: 10.1046/j.1523-1747.1999.00567.x
|View full text |Cite
|
Sign up to set email alerts
|

A Macrolactam Inhibitor of T Helper Type 1 and T Helper Type 2 Cytokine Biosynthesis for Topical Treatment of Inflammatory Skin Diseases1

Abstract: T lymphocytes play a critical part in inflammatory skin diseases but are targeted by available therapies that have only partial efficacy, significant side-effects, or both. Because psoriasis, atopic dermatitis, and allergic contact hypersensitivity are associated with T helper type 1 (Th1), T helper type 2 (Th2), or mixed Th1-Th2 cell subsets and cytokine types, respectively, there is a need for a better broad-based inhibitor. The macrolactam ascomycin analog, ABT-281, was found to inhibit potently T cell func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…We present the first objective controlled demonstration of the validity of this approach and also support most dermatologists' recommendation of applying lubrication when the skin is wet. However, this study only tested hydrating effects; its clinical effects have been reported elsewhere [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…We present the first objective controlled demonstration of the validity of this approach and also support most dermatologists' recommendation of applying lubrication when the skin is wet. However, this study only tested hydrating effects; its clinical effects have been reported elsewhere [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…It was synthesised in a search for compounds that are topically effective, but exhibit weak systemic activities following absorption. A-86281 and FK-506 showed similar topical potency in swine contact hypersensitivity assays, yet A-86281 was cleared more rapidly and was less potent when given systemically [91,92].…”
Section: Sdz 281-240 Sdz Asm 981 A-86281mentioning
confidence: 93%
“…Their key difference is the presence of an allyl group in TRL where the ascomycins feature an ethyl group. The ascomycins have been subject to extensive clinical testing in the past decade [109][110][111]. Notable members of this group are, beside the parent molecule ascomycin (FK520), pimecrolimus (SDZ ASM-981), ABT-281, and SDZ 281-240.…”
Section: Current Developmentsmentioning
confidence: 99%